(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article discusses measures to prevent and treat Covid-19 infection. Collaboration at the local, regional, national and international levels, with a focus on high-quality research, evidence-based practice, the sharing of data and resources, and upholding all ethical standards in the face of unprecedented challenges, will be key to the success of these efforts. In addition, the demand for unproven therapies can lead to shortages of drugs that are approved and indicated for other conditions, leaving patients who rely on these drugs for chronic conditions without effective therapy.